FINITE ELEMENT ANALYSIS AND EXPERIMENTAL STUDY OF COMPOSITE LEAF SPRING - Mr. Mahesh A. Khot; Prof. Sameer M. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
Leaf springs are the suspension components used in the automobile industry. For conservation of natural resources and to economize energy, weight reduction has been the focus of automobile Industries. Weight is the main issue related to the automobile industry. Thus automobile manufacturers are giving importance to reduction of weight. While reducing weight of the component designer has to think about increasing or maintaining strength of the component.